Pengaruh Pemanfaatan Teknologi Digital dan Kecerdasan Buatan terhadap Tingkat Produktivitas Mahasiswa Akuntansi - Abdullah Ariq Akbar; Agung Laksono; Dehan Akramann; Erland Ahmad Daniyal (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This research aims to study how the use of digital technology and artificial intelligence affects the productivity level of accounting students. This is based on the importance of the application of technology in the educational process, especially in accounting, which requires accuracy and efficiency. This research uses a quantitative approach by conducting a survey of 32 accounting students from several universities in Indonesia. They were selected through snowball sampling method. A Likert scale questionnaire was used to collect data and then analyzed using multiple linear regression using the SPSS program. The results showed that the use of digital technology and artificial intelligence is both positive and significant to the level of student productivity. The technology utilization variable contributed 36.7% to productivity, while the artificial intelligence variable contributed 34.9%. The results of this study indicate that the use of current technology in accounting learning not only improves the efficiency of tasks, but also improves the quality of results and students' analytical skills. Therefore, educational institutions should adopt a technology-based learning approach in order for accounting students to achieve an optimal level of academic performance.